Investigation of aggregation behavior and microstructure of hard carbon dispersions for semisolid sodium flow batteries - Hanan Dabash (22927810) (2025)
This is the first study to elucidate the aggregation mechanism and flow behavior of the dispersions of hard carbons (HCs) as a conductive matrix for semisolid sodium flow batteries. The flake–like morphology of primary particles and the surface chemistry (weakly hydrophilic surface) of HCs mediate the domination of ballistic agglomeration mechanism in presence of sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) salt. As the HCs content increases, the aggregation mechanism does not alter and, instead, tenuous network turns compact due to densification of aggregates as a consequence of increased number density of unusual short bifurcations. Consequently, the dispersions show electrical percolating threshold (10 wt.% HCs) threefold higher than their rheological threshold (3 wt.%). Moreover, compact network with numerous bifurcations exhibit reversible shear thickening as a consequence of the formation of highly anisotropic flocs under shear flow. These findings endow rigorous determination for the composition and operational conditions of conductive dispersions for semisolid flow batteries. Other Information Published in: Journal of Materials Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10853-025-11149-1